Two new species of Lepanthes from Costa Rica close to L. schizocardia (Orchidaceae: Pleurothallidinae) - Pupulin, Franco (2013)
We revise the group of species close to Lepanthes schizocardia, and we describe and illustrate two new species from Costa Rica. Lepanthes montis-narae is compared with the Panamanian L. schizocardia, from which it mainly differs by the pendent plants, the dark gray green leaves, the ovate to orbicular, subacuminate leaves, the inflorescences borne above the leaf, the petals with inequal lobes, the apical lobe ovate, acute, the lower lobe smaller than the upper lobe, narrowly ovate, the scarlet lip and the conic, apically ciliate appendix. Lepanthes sotoana is similar to L. maxillaris from Ecuador. It can be distinguished by the pendent plants, the dark gray green leaves, the inflorescences borne above the leaf, the acute lateral sepals, the lip with subfalcate lateral lobes touching each other and hiding the base of the appendix. We also illustrate for the first time L. schizocardia to facilitate species comparison.